Pemanfaatan Air Limbah Domestik Rumah Sakit Umum X Kabupaten Sampang Sebagai Penyiraman Ruang Terbuka Hijau - Mohammad Najmi Rafi Hakim; Yayok Suryo Purnomo (Jurnal Teknik Mesin, Industri, Elektro dan Informatika, 2024)
The main and supporting activities at General Hospital X include the Emergency Department (IGD), Outpatient Department, Inpatient Department, toilets, equipment washing, mosque, haemodialysis room, mortuary, nutrition, canteen, laundry installation, and laboratory. General Hospital X produces domestic wastewater and will be utilised for watering the Green Open Space in the General Hospital X area of 28,539.44 m2, with a volume of wastewater utilised of 120.2 m3 / day. The domestic wastewater from General Hospital X contains BOD5, COD, TSS, NH3-N, oil and grease, and total coliform. Before utilisation, the waste must be treated first until it reaches the proposed quality standards. Wastewater treatment is carried out using aerobic biofilter and anaerobic biofilter technology. The water requirement per 1 m2 for watering is 0.004 m3/m2/day with a watering frequency of 2 times a day.